Hand massage therapy against anxiety in surgical patients - Anggra Trisna Ajani; Milya Novera; Mega Adyna Movitaria; Aulia Asman (lppm Universitas Muhammadiyah Semarang, 2023)
Anxiety in the preoperative stage reaches 534 million people, with an incidence rate of 5-25% among those aged 5-20 years and 50% among those aged 55 years and over, causing an increase in blood pressure that hinders rehabilitation efforts. One technique to reduce anxiety during surgery is hand massage. This research aims to understand better the effect of hand massage therapy on preoperative pain at RSI Ibnu Sina Padang in 2022. This research is experimental, using a pre - post-test design with 32 samples divided equally between intervention and control groups. The research was conducted for a full week at RSI Ibnu Sina Padang, Multazam Surgical Inpatient. Information was collected using the Hamilton Anxiety Rating Scale (HARS) and analyzed with the help of the Wilcoxon and Mann-Whitney tests. Research based on the Wilcoxon test showed a difference in the severity of symptoms between the groups participating in the experiment before and after the application of hand massage therapy (p 0.0001 for both comparisons). The results of the Mann - Whitney U test showed that hand massage could reduce the level of pain experienced by surgical patients at RSI Ibnu Sina Padang (p = 0.0001).